Burden of gastroesophageal reflux disease in 204 countries and territories, 1990–2019: a systematic analysis for the Global Burden of disease study 2019 - Li, Na; Yang, Wan-Li; Cai, Mei-Hong; Chen, Xiang; Zhao, Ran; Li, Meng-Ting; Yan, Xia-Lin; Xue, Li-Wei; Hong, Liu; Tang, Ming-Yu (BMC public health, 2023)
For effective preventive strategies against GORD (gastro-esophageal reflux disease), we assessed the GORD burden from 1990 to 2019. The burden of GORD between 1990 and 2019 was evaluated globally, regionally, and nationally. Using ASIR (age-standardized incidence), ASYLDs (age-standardized years lived with disabilitys), we compared them to the GBD world population per 100,000. The estimates were based on 95% uncertainty intervals (UIs). The AAPC (average annual percent change) in incidence, YLDs, along with prevalence rates with associated 95% CIs were estimated. Data to estimate the burden of GORD are scarce till now. The global ASIR of GORD in 2019 was 3792.79 per 100,000, an increase AAPC of 0.112% from 1990. The prevalence of GORD increased with a AAPC of 0.096% to 9574.45 per 100,000. Global ASYLDs in 2019 was 73.63, an increase AAPC of 0.105% from 1990. The GORD burden varies greatly depending on the development level and geographical location. USA demonstrated the most obvious decreasing trend in burden of GORD, while Sweden had an increasing trend. That the increase in GORD YLDs was mediated primarily by the growth and aging of population, was revealed by decomposition analyses. There was an inverse relationship between SDI (socio-demographic index) and GORD-burden. Frontier analyses revealed significant scope of improvement in the status of development at all levels. GORD is a public health challenge, especially in Latin America. Some SDI quintiles had declining rates, while some countries experienced increased rates. Thus, resources should be allocated for preventative measures based on country-specific estimates.